The Future of Social Learning in Software Engineering. - Murphy-Hill, Emerson (Computer (00189162), 2014)
Building on time-honored strengths of person-to-person social learning, new technologies can help software developers learn from one another more efficiently and productively. In particular, continuous social screencasting is a promising technique for sharing and learning about new software development tools.